Pengaruh Karakteristik Auditor Terhadap Audit Delay Laporan Keuangan Pemerintah Daerah di Provinsi Jawa Tengah - wisanggeni, bagasworo ardhi, Drs. Suyatmin Waskito Adi, M.Si (2017)
Overdue financial statements reporting may cause loses in its capacity to influence decisions. Audit delay is one of the factors that affects the timeliness of financial statements. This study examines the effects of auditor characteristics on local goverment's audit delay in Center Java. This study uses 54 local governments as a selected sample with purposive sampling method. The research data is secondary data obtained from the Audit Board of the Republic of Indonesia (BPK-SEMARANG). Thedata analysis was using multiple linear regressions analysis.The analysis showed that auditor's professional proficiency, and auditor tenure does not affect the audit delay.